HUBUNGAN ANTARA PANJANG TUNGKAI DAN KEKUATAN TUNGKAI DENGAN KEMAMPUAN SEPAKSILA DALAM PERMAINAN SEPAKTAKRAW PADA MURID SD NEGERI 1 KAMPUNG BARU - Jusran S (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2019)
This research is a type of descriptive research that uses a "correlational" research design. This research aims to find out; (1) There is a relationship between leg length and sepaksila ability in the sepaktakraw game of SD Negeri 1 Kampung Baru students; (2) There is a relationship between leg strength and sepaksila ability in the sepaktakraw game of elementary school 1 students in Kampung Baru; (3) There is a relationship between leg length and leg strength together with the ability of sepaksila in the sepaktakraw game of students of SD Negeri 1 Kampung Baru. The population is all students of SD Negeri 1 Kampung Baru. The sample used was 40 male students. The technique of determining the sample is by random selection by lottery (Simple Random Sampling). Data analysis techniques used were multiple regression analysis, Pearson product moment correlation coefficient (r), and multiple correlation analysis (R) through the SPSS 22 program at a significant level Î± = 0.05. The results showed that; (1) There is a significant correlation between leg length and sepaksila ability in the sepaktakraw game of SD Negeri 1 Kampung Baru students, with a Ï value of 0.708 (Pvalue <0.05); (2) There is a significant relationship between leg strength and sepaksila ability in the sepaktakraw game of SD Negeri 1 Kampung Baru students, with a Ï value of 0.618 (Pvalue <0.05); (3) There is a significant relationship between leg length and leg strength together with sepaksila ability in the sepaktakraw game of SD Negeri 1 Kampung Baru students, obtained by Rhitung (R) value of 0.797 (Pvalue <0.05); R2 = 0.635 or 63.5% with a Fcount of 32.163, Keywords: leg length, leg strength, sepaksilla ability